Cognitive and Psychosocial Consequences of Hurricanes Katrina and Rita Among Middle-Aged, Older, and Oldest-Old Adults in the Louisiana Healthy Aging Study (LHAS) - Cherry, Katie E. (2010)
This study examined the impact of Hurricanes Katrina and Rita on cognitive and psychosocial functioning among middle-aged (45–64 years), older (65–89 years) and oldest-old adults (90 years and over) in the Louisiana Healthy Aging Study (LHAS). Analyses of pre- and post-disaster cognitive data showed storm-related decrements in working memory for the middle-aged and older adults, but not for the oldest-old adults. Regression analyses confirmed that measures of social engagement and storm-related disruption significantly predicted pre- to post-disaster differences in short-term and working memory performance for the middle-aged and older adults only. These results are consistent with a burden perspective on post-disaster psychological reactions. Implications for current views of disaster reactions are discussed.